Improving Students Skill in Writing Descriptive Text by Using Think-Talk-Write and Clustering Techniques - Herlina B; Muhammad Asfah Rahman; Amirullah Abduh (Celebes Journal of Language Studies, 2022)
The research was aimed at investigating: 1) To find out the students’ achievement in their descriptive text writing using Think-Talk-Write and Clustering Technique. 2) To find out the students’ interest in the implementation of the Think-Talk-Write and Clustering Technique in writing descriptive text. This study was a quasi-experimental research with two groups. The population of this research was the 4th and 6th semester of the English Department in the Faculty of Teacher Training and Education at Iqra Buru University. Directed took cluster random as the sample. As a result, the 22 students were selected as the experimental group and the 20 students as the control group. The data were obtained from the pretest and posttest. Then, the data were analyzed by using an independent sample t-test. The mean achievement scores of the experimental group were 64.68 bigger than the mean achievement scores of the control group was 53.05. In the pretest, the t-test for Equality of Means in the Sig. (2-tailed) was bigger than Sig. (2-tailed) in the posttest. Because The result of this research revealed that the mean achievement scores of the students in the experimental group are greater than the mean achievement scores of the students in the control group. So, there was a significant difference in correlation between the mean achievement scores of students taught using Think-Talk-Write and using the clustering technique. This suggests that the Think-Talk-Write technique facilitates the students to improve their writing achievement.